The medical necessity of advanced molecular testing in the diagnosis and treatment of brain tumor patients. Issue 12 (4th July 2019) - Horbinski, Craig; Ligon, Keith L; Brastianos, Priscilla; Huse, Jason T; Venere, Monica; Chang, Susan; Buckner, Jan; Cloughesy, Timothy; Jenkins, Robert B; Giannini, Caterina; Stupp, Roger; Nabors, L Burt; et al.
Abstract: Accurate pathologic diagnoses and molecularly informed treatment decisions for a wide variety of cancers depend on robust clinical molecular testing that uses genomic, epigenomic, and transcriptomic-based tools. Nowhere is this more essential than in the workup of brain tumors, as emphasized by the incorporation of molecular criteria into the 2016 World Health Organization classification of central nervous system tumors and the updated official guidelines of the National Comprehensive Cancer Network. Despite the medical necessity of molecular testing in brain tumors, access to and utilization of molecular diagnostics is still highly variable across institutions, and a lack of reimbursement for such testing remains a significant obstacle. The objectives of this review are (i) to identify barriers to adoption of molecular testing in brain tumors, (ii) to describe the current molecular tools recommended for the clinical evaluation of brain tumors, and (iii) to summarize how molecular data are interpreted to guide clinical care, so as to improve understanding and justification for their coverage in the routine workup of adult and pediatric brain tumor cases.